The Impact of Developing Amenities and Corridor Infrastructure in the Borobudur Area on Landscape Visual Quality - Almira, Nisrina Salsabila; Setiawan, Bakti (Universitas Negeri Yogyakarta, 2024)
The Borobudur area, a priority tourism destination in Indonesia, is renowned for its rich historical and cultural significance. To enhance its appeal and improve the tourist experience, the government has been developing infrastructure and tourism amenities along the Borobudur area corridor, with significant advancements observed in the Palbapang-Borobudur corridor. This study employs the Scenic Beauty Estimation (SBE) method, a quantitative approach designed to evaluate landscape visual quality through tourists' perceptions. A survey of 60 tourists was conducted along the Palbapang-Borobudur corridor to assess the impact of these developments. The findings reveal that the development of amenities and infrastructure enhances the visual quality, particularly in the first segment at the Palbapang Lion Gate, characterized by scenic views of the Menoreh mountains and well-integrated vegetation. Landscape elements such as terraced buildings, natural vegetation, and harmonious design contribute positively to visual perception. In contrast, segments 2, 3, and 4 score lower due to mismatched building types, colors, and the presence of visually disruptive billboards. This study highlights the need for integrated planning and management to balance tourism development with the preservation of cultural and natural landscapes. The use of the SBE method provides a novel framework for assessing visual quality in heritage areas, offering valuable insights for sustainable tourism planning in similar contexts.